Új utak a növényvédő szer engedélyezési eljárásban - Jordán, László (GEORGIKON FOR AGRICULTURE, 2023)
The authorization of the plant protection products (PPP) is an unavoidable process for the safe and effective PPP use. In the EU this procedure is extremely slow, although several initiatives have been launched in order to increase the efficiency and to speed up the registration process. In the summer of 2022, the national act on the supervision of the food chain safety was modified, allowing the dossier evaluation as part of the authorisation process to be organised on a market basis. Several profit-oriented enterprises have started to deal with this task; the preparatory work is currently underway and a new, market-based evaluation system will be launched soon. The presentation intends to present the background and the possibilities of this new system.